DESIGN ANTENNA MIMO 2X2 PATCH RECTANGULAR FOR WIFI 6 APPLICATIONON 5GHZ BAND - Endrian, Ielfandi; Kusumawardhani, Eka; Marpaung, Jannus (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
The development of wireless network technology, particularly WiFi 6 at 5GHz, offers greater reliability and data transfer capacity. Antenna design is a crucial aspect in optimizing WiFi 6 networks in complex wireless environments. The study examined a rectangular patch 2x2 MIMO Antenna for WiFi 6 at 5GHz with a focus on improving network parameters such as return loss, bandwidth, VSWR, and gain. The use of various methods and references from Balanis (2005) and Webster (2021) supports the development of antenna technology, while previous research by Ni Putu Kartika Dewi (2019) strengthens the understanding of microstrip antennas for LTE applications. The main objectives of the study were to design and simulate a rectangular patch 2x2 MIMO Antenna for WiFi 6, as well as analyze simulation data using CST Studio Suite 2019 software. This research uses hardware in the form of Acer Aspire laptops and CST Studio Suite 2019 as simulation software and antenna design. The simulation results show that this antenna is able to work in the frequency range of 4.5-5.2 GHz with a bandwidth of 55.4 MHz and return loss of -20.677981 dB, VSWR 1.2038357, and gain 3.429 dBi with omnidirectional radiation patterns. However, the addition of antenna patches has an impact on decreasing gain. This study provides an in-depth understanding of MIMO antenna design to support WiFi 6 performance in complex wireless environments.